1961
DOI: 10.1099/00221287-25-3-429
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Oxidative Activities in Escherichia coli and Bacillus megaterium in Relation to Other Changes during Inhibition of Growth by Streptomycin

Abstract: SUMMARY When the growth of cultures of Bacillus megaterium KM, Escherichia coli B orBacillus subtilis ceased following addition of streptomycin during the exponential phase of growth, harvested organisms showed oxidative activities on glucose, lactate, pyruvate and succinate which were between 20 and 60 yo of those of normal organisms. With E . coli, this reduction in oxidative activity was closely parallel to the decrease in growth rate. During the period in which growth became fully inhibited by streptomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1962
1962
2002
2002

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The present experiments show clearly that the effect of Sm on respiratory activity in B. megaterium, as in E. coli (Dubin et al, 1963), does not begin until after killing has commenced; previous experiments (Hancock, 1961) had suggested that this effect is more nearly concurrent with reduction in growth rate. Since nucleic acid is synthesized at the normal rate after viability is lost in medium AP1, it seemed probable that ATP synthesis must continue, and direct estimations show that the cellular pool of ATP does remain nearly normal until after killing has begun.…”
Section: Data)supporting
confidence: 48%
See 2 more Smart Citations
“…The present experiments show clearly that the effect of Sm on respiratory activity in B. megaterium, as in E. coli (Dubin et al, 1963), does not begin until after killing has commenced; previous experiments (Hancock, 1961) had suggested that this effect is more nearly concurrent with reduction in growth rate. Since nucleic acid is synthesized at the normal rate after viability is lost in medium AP1, it seemed probable that ATP synthesis must continue, and direct estimations show that the cellular pool of ATP does remain nearly normal until after killing has begun.…”
Section: Data)supporting
confidence: 48%
“…The earliest detectable changes were an increase in the rate of efflux of cellular K ions coinciding with a stimulation of the rate of ribonucleic acid (RNA) synthesis, followed by a specific inhibition of protein synthesis coinciding with loss of viability. To see whether a similar picture of the action of Sm is observed in other organisms, and to extend earlier observations (Hancock, 1961(Hancock, , 1962) which indicated some differences in the effect of Sm on Bacillus megaterium and E. coli, similar experiments were carried out with B. megaterium. This organism is highly sensitive to Sm, and low concentrations of the drug (4 to 5,ug/ml) were used to spread out the effects in time.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Bacillus mgaterium KM was grown in CGY medium (Hancock, 1962) adjusted to pH 7.2, except in one experiment where the pH value was deliberately changed. The conditions of growth were the same as R. HANCOCK those used earlier for this organism (Hancock, 1961). Streptomycin was added to cultures in the exponential phase of growth when the optical density (at 700 mp) was 0-6-0-7.…”
Section: Methodsmentioning
confidence: 99%